Analyzing Students’ Ability in Using Drama to Enhance Language Competence - Charles Setiawan Toedje; Desmon Moningkey (Sintuwu Maroso Journal of English Teaching, 2023)
This study will highlight students’ ability in using drama for learning English to enhance their language competence. It also elaborates both the benefits and potential disadvantages of applying drama in the classroom. This study applies descriptive qualitative methodology where interviews, classroom observation and test or proficiency examination are used to gain the data. Information from interview, observation and examination are considered as primer data. The results of the study shows that the use of drama increasing participants' language abilities, particularly ability to communicate as kind of interaction, discussion and producing better language competence and the most important things is to motivate students to be more interesting and active in the learning process. Students’ responsibility and courage to do their duties emerge during this study is an outcome also.